Corrosion Behavior of Work Hardened SnPb-Solder Affected Copper in the Bay of Bengal Water Environment - M. Muzibur Rahman; S. Reaz Ahmed; M. Salim Kaiser (Advances in Materials Science and Engineering)
Copper and its alloys are extensively used in marine applications due to high corrosion resistant behavior. But the corrosion immunity of copper varies with the environmental factors especially the sea water ingredients. Many researchers investigated corrosion level of copper materials in different oceans/seas. Unfortunately, such study is missing in the Bay of Bengal water. Moreover, inclusion of alloying elements can have influence on the corrosion behavior of copper, especially the addition of SnPb-solder for repair works and environmental effects due to ageing. In fact, the urge of using old copper to manufacture new components for marine applications necessitates the characterization of various properties. In this context, present paper is an attempt to investigate the corrosion behavior of copper and solder affected copper to enhance the reuse potential of SnPb-solder affected old/waste copper in contact of the bay water along with comparison with commercial copper alloys. Here, the result shows that overall leaching is increased for the addition of Sn and/or Pb in Cu over the whole immersion period in the stagnant water of the Bay of Bengal. The highest loss is found to be of Cu-Pb alloy which is followed by SnPb-solder affected copper, then Cu-Sn alloy and the lowest loss is of pure copper. The cold-rolled work-hardening has reduced the corrosion rate for all copper alloys. It also reveals that the solder affected copper is more corrosion resistant than commercial copper alloys such as brass and bronze.